PENGARUH KOMPENSASI, MOTIVASI, DAN MEDIASI DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT. PPI - SYIFA SABILA HADISAWA; IDA FARIDA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to analyze the influence of Compensation, Motivation, dan the Mediation of Discipline on Employee Performance at PT. PPI. The sampling technique used is saturation sampling, with a total sample of 142 respondents consisting of permanent dan non-permanent employees of PT. Pacific Prestress Indonesia (PPI). This study employed the SEM (Structural Equation Modeling) analysis method with the assistance of SmartPLS dan SPSS software for data testing. The results indicate that compensation does not affects employee performance, work motivation affects employee performance, work discipline affects employee performance, compensation affects work discipline, dan work motivation affects work discipline. However, compensation does not affects employee performance through work discipline, whereas work motivation affects employees performance through work discipline.